Optimization of the Protection Interlocking Function of a 56 MW Unit Steam Turbine - Zhiliang, Wang; Hongwei, Feng; Ihsan, Muhammad (Syntax Corporation, 2024)
There are 2 x 56MW units in Kendari power plant, each unit is equipped with two 100% capacity electric feed pumps, one running and another one backup. During the operation of the unit, two defects, such as large vibration of the BFWP and high temperature of the thrust pad on the working face, were found to affect the operation. The large vibration of the BFWP is mainly due to the falling off of the positioning pin of the bearing bracket of the non-drive end, which causes the center to sink, and the balance drum and the balance sleeve are rubbed dynamically and statically. The main reason for the high temperature of the thrust pad of the BFWP is that the diameter of the balance drum is small, which leads to an increase in the axial thrust borne by the thrust pad of the working face, and the high temperature of the tile. This study aims to diagnose the root causes of these defects, implement corrective measures, and optimize pump performance to enhance operational safety. A combination of on-site inspections, data analysis, and engineering interventions was conducted. Findings indicate that structural realignment and reengineering of the balance drum significantly mitigated vibration and temperature issues. The study concludes that proactive maintenance and design optimization are essential for the reliable operation of power plant equipment, with implications for enhancing long-term efficiency and safety.thrust padthrust pad